Development and validation of a sexual and reproductive health knowledge scale - Shih-Hui Lee; Kee-Jiar Yeo; Lina Handayani (International Journal of Public Health Science (IJPHS), 2022)
The purpose of this study was to develop a reliable and valid instrument to measure primary school students’ sexual and reproductive health (SRH) knowledge. The instrument measures primary school students’ knowledge in four domains: i) puberty; ii) human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) and sexually transmitted diseases; iii) prevention of child sexual abuse; and iv) reproduction and reproductive systems. All items in the instrument were reviewed and screened by experts before they were administered to 125 primary five students. The instrument’s dimensionality, fit statistics, hierarchical ordering of item difficulty, and item and person separation reliability were assessed using the rasch measurement model (RMM). The results showed that the instrument demonstrated unidimensionality, and the items exhibited a wide range of difficulty level. Misfitting items were removed from the questionnaire, and the remaining 36 items were retained. The RMM outputs showed good item’s reliability (.97) with high separation index (5.52). However, the person reliability (.79) and the person separation index (1.94) were slightly the recommended value. Overall, the results show that the developed instrument can be used with confidence to assess sexual and reproductive health (SRH) knowledge among primary school students in Malaysia.